Concrete flowers : a novel - N'Sondé, Wilfried (Global African voices, 2018)
Behind the bars on her window, Rosa Maria dreams of sunshine, love, calm, and leaving the city where she lives with her family. She suffers her father's beatings, hides her femininity behind shapeless clothing, and pines for the beautiful Jason as she awaits her opportunity to flee. Meanwhile, her older brother is found dead in a nearby parking lot, and the neighborhood explodes in a riot against the police. Rosa Maria resolves to act before she is devoured by family intrigues and despair. Wilfried N'Sondé's powerful voice creates a palpable sense of the absence of hope and the social and racial isolation that pervade the Paris projects, even as he never abandons the expansive capacity of individuals to dream of better lives beyond a seemingly hopeless reality.